PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TANETE RILAU KAB.BARRU - Jalali Iqram; Samsul Rizal (Universitas Muhammadiyah Makassar, 2019)
This study aims to examine the influence of organizational culture and work environment on employee performance at the Tanete Rilau District Office in Barru District partially. This research data was collected from 30 respondents who worked at the Tanete Rilau District Office in Barru District. Respondents were obtained using total sampling techniques or saturated samples. Questions are given using a questionnaire. Respondents' responses to the questions were then analyzed quantitatively which included validity, reliability and multiple linear regression analysis. The results showed that organizational culture variables have a significant effect on employee performance. This is indicated by the t count value of 4.034 greater than t table 2.052 and the significance value of 0.000 is less than 0.05. The work environment has no significant effect on employee performance. This is indicated by the value of t count of 1.107 smaller than t table 2.052 and the significance value of 0.278 is greater than 0.05. The most dominant variable influencing the performance of employees at the Office of Tanete Rilau District, Barru Regency is the organizational culture with a beta value of 0.605 greater than the beta value of the working environment variable 0.166.